11-Azaartemisinin cocrystals with preserved lactam : acid heterosynthons. Issue 9 (24th January 2018) - Nisar, Madiha; Sung, Herman H.-Y.; Puschmann, Horst; Lakerveld, Richard; Haynes, Richard K.; Williams, Ian D.
Abstract : The R22(8) lactam : acid hetero-synthon, found in several new 1 : 1 and 2 : 1 cocrystals between the anti-malarial 11-azaartemisinin and organic acids. Abstract : 11-Azaartemisinin (11-Aza) is a potent anti-malarial drug more readily able to form cocrystals than its parent compound. 13 new 1 : 1 and 2 : 1 cocrystal phases from 25 mono- and bi-functional acids are reported here in excellent yield and purity by liquid assisted grinding. X-ray structures of several of these cocrystals reveal R22(8) heterosynthons with short OH–OC H-bonds ≤2.60 Å between the 11-Aza lactam and the coformer acid groups. The new phases can show enhanced aqueous solubility of 11-Aza of 3× after 12 h. Notably diastereospecific cocrystal formation can occur, with thedl -mandelic acid system yielding solely the 11-Azaart : d -mandelic acid 1 : 1 product.